Edukasi Lama Penggunaan Kontrasepsi Hormonal Menurunkan Risiko Kanker Serviks Pada Pasangan Usia Subur - Rizka Laili, Nurul Fahmi; Prayoga, Dimas Hadi; Fatmawati, Lilis; Alfianti, Khalifatus Zuhriyah (STIKES Yayasan RS.Dr.Soetomo, 2024)
Introduction: Contraception is an effort that can be made to prevent pregnancy for certain purposes, either temporarily or permanently. There are various types of contraceptives available, including long-term contraceptives (MKJP), such as intrauterine devices (IUD), implants, female medical surgery (MOW), and male medical surgery (MOP), and non-long-term contraceptive methods. (non MKJP), such as condoms, pills and injections. The current phenomenon is the lack of public knowledge regarding the effects of prolonged use of contraception. The aim of this community service is to provide education on the duration of contraceptive use. Method: The method used in this community service is to provide education regarding the duration of contraceptive use and analyze the relationship between the duration of contraceptive use and the results of visual inspection of acetic acid. Results: This community service has a significant relationship between the duration of use of the intrauterine contraceptive device and the results of visual inspection of acetic acid. Conclusion: The use of contraception must be adjusted to the specified duration. This is because the side effects that will arise the longer the contraceptive device lasts, which affects hormones in the body